KILKA SPOSTRZEŻEŃ NA TEMAT PRAWA LITEWSKIEGO NA PRZEŁOMIE XVIII I XIX WIEKU W ŚWIETLE KSIĄG ZIEMSKICH SZAWELSKICH - Sławomir Godek (Zeszyty Prawnicze, 2016)
A FEW OBSERVATIONS ON LITHUANIAN LAW AT THE TURN OF THE 18TH-19TH CENTURY FROM THE PERSPECTIVE OF THE SZAWLE (ŠIAULIAI) LEDGERS